Characterization and Preliminary Application of Phage Isolated From Listeria monocytogenes - Li, Tianhao; Zhao, Xuehui; Wang, Xuejian; Wang, Zijian; Tian, Changqing; Shi, Wenjing; Qi, Yumei; Wei, Huilin; Song, Chen; Xue, Huiwen; Gou, Huitian (Frontiers in Veterinary Science, 2022)
Listeria monocytogenes (LM) is one of the four major foodborne bacteria that cause bacteremia and meningitis. To explore the control of listeriosis with natural phages, we used the double layer agar plate method to isolate LM from slaughterhouse sewage and designated LP8. The result of electron microscopy indicated the phage was belonged to the family of Myoviridae. Whole-genome sequencing indicated that the genome size of LP8 is 87,038 bp and contains 120 genes. Mice were infected with LM and treated with penicillin G sodium, LP8 and their combination individually. From the levels of lymphocyte subsets (CD4+, CD8+), the expression of cytokines (TNF-ɑ, IL1β, IL-10, IFN-γ), observation of pathological changes of organs (heart, liver, spleen, kidne, brain), and the bacterial load of the spleen, we concluded therapeutic effect of LP8 against listeriosis and demonstrate the feasibility of a combined therapy to reduce the use of antibiotics. This provide a new avenue for the treatment of listeriosis.